Captain America. Brave new world [videorecording (DVD)] - Onah, Julius, 1983-; Edwards, Rob, 1963-; Spellman, Malcolm; Musson, Dalan; Glanz, Peter; Mackie, Anthony, 1978-; Ramirez, Danny, 1992-; Haas, Shira, 1995-; Lumbly, Carl; Roquemore, Xosha; Esposito, Giancarlo; Tyler, Liv; et al. (Marvel Studios, 2025)
As he takes on the mantle of Captain America, Sam Wilson meets with newly elected U.S. president Thaddeus Ross and soon finds himself in the middle of an international incident. In a race against time, Sam must unravel a nefarious global plot before the true mastermind has the entire world seeing red.